Quality management practices in construction projects in the context of Malaysian construction industry - Tan, Chin Keng; Abdul Rahman, Hamzah (2009)
There is a gap of understanding on the practices of quality management in the building construction projects in the context of Malaysian construction industry as similar researches are hardly obtained from the literatures reviewed. This research is conducted to minimize such gap of understanding. It aims to identify the constructs of quality management practices and explore the practices of quality management in building construction projects in the context of Malaysian construction industry through a questionnaire survey. The research findings reveal that there are weaknesses in the practices of quality management at the aspects cost of quality, information and analysis, quality attitude and culture, customer focus, and continuous improvement and sustainability. It is recommended that the construction organizations to enhance their awareness and commitment on the implementation of formal quality management system to improve the weaknesses in their quality management practices.